2013
DOI: 10.1016/j.neuron.2013.09.036
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Amygdala Lesions on Reward-Value Coding in Orbital and Medial Prefrontal Cortex

Abstract: SUMMARY We examined the contribution of the amygdala to value signals within orbital (OFC) and medial (MFC) prefrontal cortex. On each trial, monkeys chose between two stimuli that were associated with different quantities of reward. In intact monkeys, as expected, neurons in both OFC and MFC signaled the reward quantity associated with stimuli. Contrasted with MFC, OFC contained a larger proportion of neurons encoding reward quantity and did so with faster response latencies. Removing the amygdala eliminated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
145
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(163 citation statements)
references
References 50 publications
17
145
1
Order By: Relevance
“…Further analysis confirmed that neurons consistently coded features of the currently presented offer, regardless of other variables. For instance, neurons used similar codes for the water amounts of the informative and non-informative offers, and did not have a predominant tendency to encode the water amount of the second offer relative to the previously presented first offer (Figure S4) consistent with previous studies (Rudebeck et al, 2013). …”
Section: Resultssupporting
confidence: 81%
“…Further analysis confirmed that neurons consistently coded features of the currently presented offer, regardless of other variables. For instance, neurons used similar codes for the water amounts of the informative and non-informative offers, and did not have a predominant tendency to encode the water amount of the second offer relative to the previously presented first offer (Figure S4) consistent with previous studies (Rudebeck et al, 2013). …”
Section: Resultssupporting
confidence: 81%
“…Enhanced positive coupling between vmPFC and Amyg and vStr regions may indicate the propagation of a stronger motivational signal for the tastier item into value computations. However, although previous studies have shown that activity in these areas can influence reward value coding in vmPFC regions (Hampton et al, 2007;Jenison, 2014;Rudebeck et al, 2013), we note that the PPI analyses we conducted do not indicate the direction of signaling between regions or the presence of monosynaptic connections. Overall, these results are consistent with the idea that these Amyg and vStr signals may be linked to the influence of taste on valuation and choice.…”
Section: Discussioncontrasting
confidence: 82%
“…The stronger encoding of relative taste value in areas such as Amyg and vStr that signal the motivational value of objects (Miller et al, 2014), together with their greater functional connectivity to vmPFC at the time of a tastier choice, suggests a potential mechanism for increasing the importance of taste in the value computation processes (Hampton et al, 2007;Jenison, 2014;Rudebeck et al, 2013), and subsequently in the observed choices of the stressed participants, especially those with a stronger HPA axis response to the stressor. It may be that acute stress results in enhanced reward salience or stronger wanting (Berridge, The Three Factor Eating Questionnaire (TFEQ), Spielberger State-Trait Anxiety Inventory (STAI), and Behavioral Inhibition & Activation Scales (BIS/BAS) were administered in the waiting period at the end of the study.…”
Section: Fmrimentioning
confidence: 99%
“…The amygdala is also involved in learning and decision-making: neuronal activity in the amygdala tracks signed reward values, in which either appetitive or aversive outcomes are signaled by distinct but anatomically-intermingled populations of neurons [15]. Amygdala lesions impair, but do not abolish, reward value coding by neurons in prefrontal cortex [16]. Converging evidence from humans and other animals suggests that reward-related computations are tightly associated with social behavior [9,17].…”
Section: Social Behavior and The Amygdalamentioning
confidence: 99%
“…While it has previously been shown that bacterial biofilms can promote growth of different bacteria, Fox et al [8] report for the first time that fungal biofilms can also support growth of two obligate anaerobes found in the human GI tract, Clostridium perfringens and Bacteroides fragilis [16]. As C. perfringens and B. fragilis are anaerobes with differing degrees of tolerance to oxygen, the authors' hypothesized that C. albicans biofilms contain regions of reduced oxygen levels, or hypoxic microenvironments.…”
Section: Robert a Cramermentioning
confidence: 99%